Status and risk assessment of heavy metal pollution in farmland soil in the southern suburbs of Jiaozuo City - Fan, Chengmeizi (International Journal of Natural Resources and Environmental Studies, 2024)
A farmland in the southern suburb of Jiaozuo City was selected As the research area, 36 surface soil samples were collected, and the contents of heavy metals (Cd, Cr, Zn, Ni, Cu, Pb and As) in soil were determined. The ecological risk of heavy metals in soil was assessed by single factor pollution index method, Nemerow comprehensive pollution index method and potential ecological risk index method. The results showed that the average contents of Cd, Cr, Zn, Ni, Cu, Pb and As in the soil were 1.25, 62.96, 79.00, 28.91, 22.60, 11.02 and 42.25mg/kg, respectively. Cd and As in soil exceeded the standard, and the exceedance rate was 92.75% and 83.5%. The single factor pollution index was Cd>As>Cr>Zn>Cu>Ni>Pb from large to small, and Cd reached the moderate pollution level. The results of Nemerow comprehensive pollution index showed that Cd reached the level of severe pollution, and As was the level of severe pollution. The evaluation results of potential ecological risk index showed that Cd was at the moderate risk level, As was at the slight risk level, and other heavy metals were at the slight risk level. The comprehensive potential ecological risk index RI value was 13.87-266.80, which was at the slight to moderate risk level. Cd and As were the main risk sources of soil heavy metals, and their contribution rates to the comprehensive potential ecological risk index were 79% and 18%, respectively.